PENINGKATAN KETERAMPILAN BERBICARA BAHASA ARAB MELALUI METODE BERNYANYI PADA ANAK KELOMPOK B DI PAUD AL-MADANIY GONDANGLEGI-MALANG - Amalia , Dahlia; Rohmawati, Afifatu (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2020)
Improving Arabic speaking skills through singing method which shows that there are problems in learning Arabic for children who have developed at each school are less attractive. Thus, researchers designed the concept of learning Arabic using the method of singing. This research uses the type of Classroom Action Research (Action Research). Data collection techniques through the application of cycles, and documentation. Based on the findings show that there is an increase in Arabic speaking skills through the method of singing which is shown through an increase in mastery learning with a percentage of 30%. The increase in the first cycle with a percentage of 53% and an increase in the second cycle with a percentage of 83%. So, the improvement of Arabic speaking skills through singing method in group B children between cycle I to cycle II was 30%. In the results obtained the singing method is very effective and efficient in improving Arabic speaking skills through memorization techniques.